TRANSFORMING TEACHERS' INNOVATIVE BEHAVIOR BASED ON MANAGEMENT OF KULLIYYATU-L-MU'ALLIMĪN AL-ISLĀMIYYAH - Maharani Nubdzah Fithroty; Syarifan Nurjan; Muh. Tajab; Aldo Redho Syam (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2025)
Innovative behavior among teachers is vital in addressing educational challenges in the era of globalization, particularly in pesantren environments that integrate religious and general education. This research examines the transformation of teachers' innovative behavior based on the management of Kulliyyatu-l-Mu'allimīn Al-Islāmiyyah (KMI) at Pondok Modern Al Barokah. The study aims to analyze the roles of transformational leadership, teacher self-efficacy, and organizational support in fostering innovative behaviors within the KMI framework. Using a qualitative approach, the research employs case studies through in-depth interviews, observations, and document analysis. Data were analyzed using Spradley’s model, which includes domain, taxonomy, component, and cultural theme analysis. Validity tests were based on credibility, transferability, dependability, and confirmability. The study reveals that the transformation of teachers’ innovative behavior at Pondok Modern Al Barokah is influenced by two main factors. First, transformational leadership motivates teachers to explore new teaching methods and integrate technology, despite existing limitations. Second, increased teacher self-efficacy, facilitated by continuous training and collaborative experiences, encourages creative teaching practices. Organizational support, such as flexible policies and the establishment of Professional Learning Communities (PLCs), strengthens innovation and promotes collaboration among teachers. The integration of both religious and public curricula fosters holistic learning innovations. This research offers practical contributions for Islamic boarding school administrators and educational institutions, guiding the design of management strategies that support teacher innovation. Theoretical implications highlight the role of self-efficacy and organizational support in enhancing transformational leadership and innovative behaviors in the context of faith-based education.